Rofecoxib-induced deleterious effects escape detection by organismal performance assays (Journal of Pharmaceutical Negative Results, 2016)
Background: Organismal performance assays (OPAs) are a unique method of toxicity quantification used to assess the safety of potentially toxic compounds such as pharmaceuticals. OPAs utilize genetically diverse wild mice (Mus musculus) housed in large seminatural enclosures wherein exposed individuals compete directly with controls for resources. Previously, OPAs have been successful in detecting adverse effects in mice that were exposed to paroxetine. Here, we further test OPAs’ utility in pharmaceutical safety assessment by testing OPAs with rofecoxib, a drug with known adverse effects on humans. Materials and Methods: We exposed mice to rofecoxib (~37.5 mg/kg/day) during gestation and into early adulthood. Exposure ceased when individuals were released into enclosures. Five independent populations were established and rofecoxib‑exposed individuals (n = 58) competed directly with control individuals(n = 58) over 28 weeks. Organismal performance was determined by quantifying reproduction, survival, and male competitive ability. Results: In enclosures, rofecoxib‑exposed males had equal reproduction, survival, and competitive ability. Rofecoxib‑exposed females had equal survival compared to controls but experienced 40% higher reproductive output. Conclusions: The adverse health effects of rofecoxib seen in humans escaped detection by OPAs, just as they had during traditional preclinical assays. These results may be explained by the exposure design (in the enclosures, all animals were on the control diet), the relatively short duration of exposure, species differences, or because the health benefits of the drug negated the side effects. Similar to numerous assays used in preclinical trials, OPAs cannot reveal all maladies, despite their demonstrated sensitivity in detecting cryptic toxicity from numerous exposures.